Enhanced performance of perovskite solar cells with solution-processed n-doping of the PCBM interlayer. Issue 69 (11th July 2016) - Bae, Jun-Ho; Noh, Yong-Jin; Kang, Minji; Kim, Dong-Yu; Kim, Hyun-Bin; Oh, Seung-Hwan; Yun, Jin-Mun; Na, Seok-In
Abstract : Here, we report a facile and efficient sequential n-doping method to increase the device performance of planar-type organic/inorganic perovskite solar cells. Abstract : Here, we report a facile and efficient sequential n-doping method to increase the device performance of planar-type organic/inorganic perovskite solar cells. Compared to the pristine PCBM-based electron transport layer (ETL), power conversion efficiencies of cells with a doped ETL are dramatically enhanced up to 12.53%.